1998
DOI: 10.1016/s0895-7061(98)00017-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Differences Between Metoprolol and Carvedilol in Hypertensive Patients

Abstract: Resting hemodynamics were measured before, at 2 and 24 h after the first dose, and after 4 weeks of monotherapy with either metoprolol or carvedilol in a randomized single-blind study. We analyzed results from 24 hypertensive patients (30-68 years of age) with adequate blood-pressure lowering on monotherapy. Acutely, both drugs lowered systolic blood pressure and heart rate. Whereas metoprolol reduced cardiac output and increased both systemic and femoral artery resistance, carvedilol did not alter cardiac out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These results are compatible with the previous clinical findings showing that carvedilol decreases vascular resistance, while metoprolol does not. 25) It has been reported that carvedilol inhibits prostaglandin F 2α -induced contraction in VSM. 8,35) The present study also showed that carvedilol inhibits [Ca 2+ ] i rise through Ca 2+ entry elicited by vasopressin and endothelin-1.…”
Section: Discussionmentioning
confidence: 98%
“…These results are compatible with the previous clinical findings showing that carvedilol decreases vascular resistance, while metoprolol does not. 25) It has been reported that carvedilol inhibits prostaglandin F 2α -induced contraction in VSM. 8,35) The present study also showed that carvedilol inhibits [Ca 2+ ] i rise through Ca 2+ entry elicited by vasopressin and endothelin-1.…”
Section: Discussionmentioning
confidence: 98%
“…The sympathetically mediated reflex tachycardia that usually accompanies peripheral vasodilation does not occur with carvedilol because of its nonselective cardiac â-adrenoceptor antagonist activity (86,90). In a randomized, single-blind study of 24 hypertensive patients, Weber et al (110) compared the resting hemodynamic effects of carvedilol (25 mg daily) and metoprolol (100 mg daily). Either drug lowered systolic blood pressure and heart rate by acute (2 h) or chronic (4 weeks) administration.…”
Section: Therapeutic Use Hypertensionmentioning
confidence: 99%
“…Whether these findings can be extended to other conventional, non‐vasodilating β‐blockers needs further investigation. Previous studies have confirmed that carvedilol, but not β−1 selective blockers, provides afterload reduction [1012].…”
Section: Discussionmentioning
confidence: 82%